Potentiality and Threats of Avocado Farming in Eastern Hills of Nepal - Wagle, Shyam Prasad (Bouddhik Abhiyan (बौद्धिक अभियान), 2023)
Innovative and profitable agriculture has become indispensable for the supply of food and nutrients to people as well income generation. Thus, this study deals with the feasibility of commercial avocado farming including the analysis of problems related to this especially in the case of eastern hilly areas of Nepal. This study applied household questionnaire survey, key informant survey, focus group discussions and field observation to collect relevant primary information. Previous research journals, dissertations, books and official records were used as the major sources of secondary data collection. This study covers the entire area of Ward No. 3 of  Dhankuta Municipality. Around, 44 percent (223hhs) farm households were selected as a sample out of the total 506 households of this area based on Yamane's sample determination formula (1967).This study proves that the agriculture system can be made profitable and useful through carefully using of new high valued crops. It reveals that avocado is a new commercial crop with maximum potential in the hilly areas of eastern including both challenges and opportunities. Moreover, this study also confirms that the avocado farming is not only a profitable business but also a risky and challenging. The farmers are facing various socio-economic challenges while doing this cultivation. Thus, the conclusion of the study is that the new agricultural activities are not free from challenges so that farmers must be faced patently to achieve success. This conclusion conveys the message that the success achieved only by facing barriers is sustainable.